2021
DOI: 10.15376/biores.16.3.5646-5666
|View full text |Cite
|
Sign up to set email alerts
|

Sulfomethylation of radiata pine kraft lignin and its use as a molybdenite depressant in selective chalcopyrite-molybdenite separation by flotation

Abstract: Sulfomethylation of radiata pine kraft lignin was performed using formaldehyde and sodium sulfite under alkaline conditions to determine its potential as a mineral depressant for the separation of molybdenite and chalcopyrite by froth flotation. Optimal conditions for the sulfomethylation reaction were 20% (w/w) Na2SO3 at 130 °C for 4.2 h, which resulted in lignin with a sulfonate content of 2.2 mmol/g. Microflotation assays showed that the optimized sulfomethylated kraft lignin (OSKL) depressed the molybdenit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
0
3
0
3
Order By: Relevance
“…Previous reports have revealed that kraft lignin (KL) has the potential to be a good depressant [ 12 ]. This is a promising and renewable material mainly derived from the paper industry [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have revealed that kraft lignin (KL) has the potential to be a good depressant [ 12 ]. This is a promising and renewable material mainly derived from the paper industry [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…This resulted in an increase in its hydrophilicity and electronegativity. Vidal et al sulfomethylated radiata pine kraft lignin and utilized it as a depressant for molybdenite, achieving the successful flotation separation of chalcopyrite and molybdenite [ 12 ]. Additionally, Sun et al indicated that the sulfonic acid groups of calcium lignosulphonate (CLS) interact strongly with the Ca sites on the surface of calcite, chemically adsorbing as Ca−SO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…A análise de infravermelho (FTIR) do licor negro (Figura 13A) apresentou semelhança ao FTIR de um lignosulfonato comercial (Figura 13B). A banda intensa em 1042 cm -1 pode ser atribuída a ligações S=O e várias bandas de média intensidade entre 800 cm -1 e 400 cm -1 são atribuídas a ligações S-O e C-S dos grupos sulfônicos ligados à lignina (VIDAL et al, 2021).…”
Section: Caracterização Dos Licores De Pré-tratamentounclassified
“…Os dados mostram que o teor de carbono aumentou após a ultrafiltração, o que parece estar associado com a remoção expressiva de compostos inorgânicos do licor. O teor de carbono estimado para os lignosulfonatos purificados foi de 45% para ambas as amostras, sendo condizente ao teor encontrado na literatura para lignosulfonatos (GUTIERREZ et al, 2020;VIDAL et al, 2021).…”
Section: Análise De Chns E Massa Molar Dos Lignosulfonatosunclassified
See 1 more Smart Citation